Improved impact assessment of micropollutants release from WWTPs. (May 2022) - Servien, R.; Leenknecht, C.; Bonnot, K.; Rossard, V.; Latrille, E.; Mamy, L.; Benoit, P.; Hélias, A.; Patureau, D.
Abstract: During wastewater treatment, incomplete elimination of micropollutants occurs. Recently, the potential impacts of the release of some micropollutants at the scale of France have been studied. These impact calculations were incomplete due to a lack of characterization factors (CFs). In the present study, we used already developed machine learning models to complement the missing CFs. The conclusions were not modified for the impact on aquatic environment, but were mitigated for the impact on human health: the higher toxicological potential impact could be driven by a high-emitted mass, and a high number of compounds could take a significant part of the overall impact. Graphical abstract: Image 1 Highlights: Machine learning models were used to estimate missing characterization factors (CFs). This allowed complementing impact assessment of micropollutants release from WWTPs. The impact resulted of a high-emitted mass or a high toxicological potential. This work will help to select substances to work on for environmental restoration. It could be easily adapted to any other compartment or geographical context.